A new species and new records of Pachytullbergiidae and Tullbergiidae (Collembola: Onychiuroidea) from littoral of China, with notes on the variations of postantennal organ - Bu, Yun; Potapov, Mikhail B.; Gao, Yan (Zootaxa, 2013)
Sensiphorura oligoseta sp. nov. is described from the sand beach of Pacific coast of China. It is the second member of the genus and differs from S. marshalli Rusek, 1976 by the smaller apical vesicle on antennae, and fewer setae on abdominal tergites. Psammophorura neocaledonica Thibaud & Weiner, 1997 and Mesaphorura yosii (Rusek, 1967) are also found to be widely distributed on the coast. Chinese specimens of P. neocaledonica are described, notes to variations of its post-antennal organ are given.